Steepening of waves at the duskside magnetopause. Issue 14 (25th July 2016) - Plaschke, F.; Kahr, N.; Fischer, D.; Nakamura, R.; Baumjohann, W.; Magnes, W.; Burch, J. L.; Torbert, R. B.; Russell, C. T.; Giles, B. L.; Strangeway, R. J.; Leinweber, H. K.; et al.
Abstract: Surface waves at the magnetopause flanks typically feature steeper, i.e., more inclined leading (antisunward facing) than trailing (sunward facing) edges. This is expected for Kelvin‐Helmholtz instability (KHI) amplified waves. Very rarely, during northward interplanetary magnetic field (IMF) conditions, anomalous/inverse steepening has been observed. The small‐scale tetrahedral configuration of the Magnetospheric Multiscale spacecraft and their high time resolution measurements enable us to routinely ascertain magnetopause boundary inclinations during surface wave passage with high accuracy by four‐spacecraft timing analysis. At the dusk flank magnetopause, 77%/23% of the analyzed wave intervals exhibit regular/inverse steepening. Inverse steepening happens during northward IMF conditions, as previously reported and, in addition, during intervals of dominant equatorial IMF. Inverse steepening observed under the latter conditions may be due to the absence of KHI or due to instabilities arising from the alignment of flow and magnetic fields in the magnetosheath. Key Points: The MMS spacecraft configuration, orbits, and data resolution enable us to ascertain magnetopause (wave) inclinations with high accuracy Inverse wave steepening (steeper trailing edges) occurs also when the IMF is in the GSM x‐y plane, not only during mainly northward IMF Inverse steepening may be associated to the absence of KHI or to instabilities from the alignment of flow and magnetic fields in the sheath